“The Wall was Too High”: the Four Predicaments of Mr Miliband - Eric Shaw (Revue Française de Civilisation Britannique)
This article discusses why the Labour party was highly unlikely to win the British general election of 2015. It does so by probing four major predicaments: lack of confidence in Ed Miliband as a potential Prime Minister, in Labour’s ability to run the economy, in its capacity to manage the explosive issue of immigration and in its will to tackle (alleged) pervasive welfare abuse. The article agrees that, in the key issues of the economy, immigration and social welfare Labour was quite out of tune with public perceptions and attitudes but then suggests these many of these were, in turn, at variance with empirically verifiable facts. The article then contends that political parties do have the capacity to modify public perceptions and attitudes but only be devising plausible alternative narratives. This the Labour party signally failed to do, disabling its capacity to resolve any of its four predicaments.